How creepy is your smart speaker? (Economist, 2019)
The article discusses the privacy concern over the use of smart speakers. Amazon, Apple, Google and other technology companies have reported higher sales of their smart speakers. Users of smart speakers have raised questions about their possible infiltration by hackers and exploitation of information to target online advertisements.